What Do Job Candidates Consider Important When Assessing an Academic Position?. Issue 2 (3rd May 2016) - Honeycutt, Earl D.; Thelen, Shawn T.
Abstract : Surveyed job candidates and academic mavens differ in regard to what the candidates should consider most important (e.g., quality-of-life issues, characteristics of the position, and school/department dynamics) when interviewing for an academic position. A principal finding is that candidates weigh quality of life as the most important issue, while mavens weigh the job as being most important. This suggests that candidates view aspects of the academic position much more broadly than do the mavens who prepare them for market and engage in the job interview. Also, there were conflicting attitudes about what should and should not be asked by both sides involved in the interview process. A full discussion of the study's findings is provided and suggestions are offered for making the academic hiring process more efficient.